THE ALIGNMENT OF ROMANIA UNIVERSITY TEACHING TO THE REQUIREMENTS OF THE QUALITY INSURING STANDARDS - Elena CONDREA; Liliana NICODIM (Management & Marketing)
Due to any institution in the national teaching system, indifferent of type, level and activity organization form, is to insure the quality teaching, learning and researching, from the necessity of making the bases of an institutional cultures of the education's quality, for contributing to the personal and professional development of the students, at the society's welfare. The quality insurance policies and strategies of the national teaching system of Romania have as marking the permanent correlation with the orientations and actions promoted at European and global level, in consense with the recommendations of the Superior Education Quality Insurance European Association, recommendations which have been taken by the Bergen Ministerial Conference (19-20 May 2005).